Microstructure and phase analysis of ethyl silicate-bonded alumina-zircon refractories - Sarydikmen, H; Kushkonmaz, N (CONSULTANTS BUREAU/SPRINGER, 2005)
Alumina-zircon refractories are prepared using an aqueous ethyl silicate solution as the gel-polymerized bond. Test specimens are heat-treated by reaction sintering at different temperature (1450 - 1600 degrees C) and holding times (I - 4 h) to yield new refractory phases zirconium dioxide and mullite. The specimens are tested for strength, porosity, sintering shrinkage, apparent density, and chemical and phase composition using x-ray diffractometry and electron scanning microscopy. Reactive sintering is shown to be a effective route towards obtaining ethyl-silicate-bonded alumina-zircon refractories with tailored microscopic and physical properties.
Keywords: Materials Science